Copoazu and Inclusive Businesses: A Socioeconomic Strategy in Florence, Caqueta (Colombia) - Chaparro Orozco, Ángel Alberto; López Rodríguez, Campo Elías (Cooperativismo & Desarrollo, 2017)
Introduction: In recent years, the department of Caquetá has been characterized by high rates of poverty, violence and inequality. In addition, this area has been noted for being one of the most affected by the Colombian armed conflict effects. Under these circumstances, the development of a medium-term inclusive business model, from the production and marketing of copoazú in the city of Florencia, Caquetá, could be a positive contribution to mitigate the scourge of violence and reduce poverty rates in the region.Methodology: This research presents a qualitative approach developed through a literature review.Results: The need to propose this model in the region becomes evident. The model emerges from the national government’s support through the policies proposed in the new government plan "Todos por un nuevo país 2014-2018" (All united for a new country 2014-2018), created by the presidency. The plan includes issues such as new territories of peace, a socio-economic inclusion agenda, generation of new sectors based on innovation, agriculture and rural development.Conclusions: This research is expected to represent an important contribution for the private sector and its research and development activities in infrastructure, technology and innovation.
Keywords: Caquetá; economic development; Florencia; inclusive business; productivity